The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1002/pits.20539
|View full text |Cite
|
Sign up to set email alerts
|

Using the TELLS prereading procedure to enhance comprehension levels and rates in secondary students

Abstract: A multiple-baseline design was used to evaluate the effects of the Title, Examine, Look, Look, and Setting (TELLS) prereading procedure on reading comprehension in 3, ninth-grade students with reading skills deficits. Results suggest that the TELLS procedure enhanced both comprehension levels and rates across all three students. These comprehension skills, however, did not appear to generalize across passages, suggesting that TELLS may be an effective, but not a particularly efficient prereading strategy. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Hale et al (2011) also found a strong correlation between median aloud C-rate scores and BRC scores with sixth-, seventh-, and eighth-grade samples ( r = .723). Researchers using group and within-student repeated-measures designs demonstrated that aloud C-rate was sensitive and stable enough to evaluate treatments and detect differential treatment effects (Freeland et al, 2000; Hale et al, 2005; McDaniel et al, 2001; Ridge & Skinner, 2011; Skinner, Robinson, Adamson, Atchison, & Woodward, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Hale et al (2011) also found a strong correlation between median aloud C-rate scores and BRC scores with sixth-, seventh-, and eighth-grade samples ( r = .723). Researchers using group and within-student repeated-measures designs demonstrated that aloud C-rate was sensitive and stable enough to evaluate treatments and detect differential treatment effects (Freeland et al, 2000; Hale et al, 2005; McDaniel et al, 2001; Ridge & Skinner, 2011; Skinner, Robinson, Adamson, Atchison, & Woodward, 1998).…”
Section: Methodsmentioning
confidence: 99%